2021
DOI: 10.3389/fcell.2020.625717
|View full text |Cite
|
Sign up to set email alerts
|

Haspin Modulates the G2/M Transition Delay in Response to Polarization Failures in Budding Yeast

Abstract: Symmetry breaking by cellular polarization is an exquisite requirement for the cell-cycle of Saccharomyces cerevisiae cells, as it allows bud emergence and growth. This process is based on the formation of polarity clusters at the incipient bud site, first, and the bud tip later in the cell-cycle, that overall promote bud emission and growth. Given the extreme relevance of this process, a surveillance mechanism, known as the morphogenesis checkpoint, has evolved to coordinate the formation of the bud and cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…We found that there were no major defects in chromatin segregation in the individual single mutants that disrupt one pool of Ipl1 Aurora B kinetochore localization (Figure 4E). However, depletion of both Ctf19 and Bub3 resulted in a strong defect in chromatin segregation, with 47% of cells with uneven chromatin masses between the mother and the bud, which agrees with previous findings in the literature (Garcia-Rodriguez et al, 2019). Loss of the haspin and Ndc10 pathways, combined with Bub3-depletion did not display an enhanced defect (Figure 4E).…”
Section: The Pools Of Ipl1 Aurora B At the Inner Centromere And Kinet...supporting
confidence: 91%
See 3 more Smart Citations
“…We found that there were no major defects in chromatin segregation in the individual single mutants that disrupt one pool of Ipl1 Aurora B kinetochore localization (Figure 4E). However, depletion of both Ctf19 and Bub3 resulted in a strong defect in chromatin segregation, with 47% of cells with uneven chromatin masses between the mother and the bud, which agrees with previous findings in the literature (Garcia-Rodriguez et al, 2019). Loss of the haspin and Ndc10 pathways, combined with Bub3-depletion did not display an enhanced defect (Figure 4E).…”
Section: The Pools Of Ipl1 Aurora B At the Inner Centromere And Kinet...supporting
confidence: 91%
“…However, whether the haspin kinase pathway is functional for Ipl1 Aurora B inner centromere recruitment in budding yeast is currently debated (Campbell and Desai, 2013;Edgerton et al, 2016;Galli et al, 2020;Nespoli et al, 2006;Panigada et al, 2013). In addition, budding yeast have two additional pathways that control Ipl1 Aurora B localization, through the inner centromere protein Ndc10 and through the COMA complex (Cho and Harrison, 2011;Fischbock-Halwachs et al, 2019;Garcia-Rodriguez et al, 2019;Yoon and Carbon, 1999). Whether these four pathways contribute to Aurora B's role in error correction during meiosis compared to mitosis has not been tested.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, loss of H3-Thr3 phosphorylation results in chromosomal segregation defects [ 1 , 5 ]. Other roles for Haspin have been reported in the coupling of cell-cycle progression to polarization dynamics [ 6 , 7 , 8 , 9 ], chromatid cohesion [ 10 , 11 ], organization of microtubule organizing centers (MTOCs) during murine meiosis [ 12 ], and asymmetrical histone inheritance [ 13 ] and migration [ 14 ], and Haspin inhibitors have a well-established anticancer activity [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%